A multicenter study of primary graft failure after infant heart transplantation: Impact of extracorporeal membrane oxygenation on outcomes. (7th November 2013) - Kaushal, S.; Matthews, K. L.; Garcia, X.; Wehman, B.; Riddle, E.; Ying, Z.; Nubani, R.; Canter, C. E.; Morrow, W. R.; Huddleston, C. B.; Backer, C. L.; Pahl, E.
Abstract Primary graft failure is the major cause of mortality in infant HTx. The aim of this study was to characterize the indication and outcomes of infants requiring ECMO support due to primary graft failure after HTx. We performed a retrospective review of all infants (<1 yr) who underwent Htx from three institutions. From 1999 to 2008, 92 infants (<1 yr) received Htx. Sixteen children (17%) required ECMO after Htx due to low cardiac output syndrome. Eleven (69%) infants were successfully weaned off ECMO, and 9 (56%) infants were discharged with a mean follow‐up of 2.3 ± 2.5 yr. Mean duration of ECMO in survivors was 5.4 days (2–7 days) compared with eight days (2–10 days) in non‐survivors (p = NS). The five‐yr survival rate for all patients was 75%; however, the five‐yr survival rate was 40% in the ECMO cohort vs. 80% in the non‐ECMO cohort (p = 0.0001). Graft function within one month post‐Htx was similar and normal between ECMO and non‐ECMO groups (shortening fraction = 42 ± 3 vs. 40 ± 2, p = NS). For infants, ECMO support for primary graft failure had a lower short‐term and long‐term survival rate vs. non‐ECMO patients. Duration of ECMO did not adversely impact graft function and is an acceptable therapy for infants after HTx for low cardiac output syndrome.